Simulation-Based Learning in Higher Education: A Meta-Analysis. (August 2020) - Chernikova, Olga; Heitzmann, Nicole; Stadler, Matthias; Holzberger, Doris; Seidel, Tina; Fischer, Frank
Simulation-based learning offers a wide range of opportunities to practice complex skills in higher education and to implement different types of scaffolding to facilitate effective learning. This meta-analysis includes 145 empirical studies and investigates the effectiveness of different scaffolding types and technology in simulation-based learning environments to facilitate complex skills. The simulations had a large positive overall effect: g = 0.85, SE = 0.08; CIs [0.69, 1.02]. Technology use and scaffolding had positive effects on learning. Learners with high prior knowledge benefited more from reflection phases; learners with low prior knowledge learned better when supported by examples. Findings were robust across different higher education domains (e.g., medical and teacher education, management). We conclude that (1) simulations are among the most effective means to facilitate learning of complex skills across domains and (2) different scaffolding types can facilitate simulation-based learning during different phases of the development of knowledge and skills.